The February 1948 Crisis in Czechoslovakia: Reaction, Assessments And Consequenses for the USA Foreign Policy - Artem V. Zorin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2022)
Introduction. The article examines the reaction of American diplomatic, political and media circles, who were involved in the development of the US political course and the formation of mass sentiments, to the crisis in Czechoslovakia in February 1948. It reveals connections between the perceptions of political processes in Eastern Europe by various segments of the American political elite and the nature of political decisions made by the US government.